Can Virtual Leadership Work in Tanzanian Healthcare? Examining SME and Large Provider Practices - Mutalemwa, Darlene; Ntalindanya , Ernest Michael; Issa, Faisal (Universitas Airlangga, 2025)
Background: The COVID-19 pandemic forced healthcare organisations to adapt rapidly, propelling them into a virtual work environment. Objective: This study delves into the experiences of three hospitals in Dar es Salaam, Tanzania, showcasing how leaders and their teams navigated this shift in diverse settings: two small and one large private hospital. Method: All 30 interviews generated insightful responses, but this small-scale study draws upon the 19 answers that best captured the core themes and findings from the conducted research. Results: Our results show that transitioning teams to the digital space presents challenges different from those of face-to-face teams, requiring leaders and followers to show agility. However, the research also suggests that virtual team members become more productive under the right conditions. Conclusion: Highlighting a gap in the literature, this study offers critical insights that deliver a glimpse of virtual work in Tanzanian hospitals from two small and one large public hospital. Keywords: COVID-19; Virtual work; Tanzanian SME Healthcare leadership; Tanzanian Large firm Healthcare Leadership; Team dynamics.